Phytochemicals as Regulators of Tumor Glycolysis and Hypoxia Signaling Pathways: Evidence from In Vitro Studies - Ioana-Ecaterina Pralea; Alina-Maria Petrache; Adrian Bogdan Tigu; Diana Gulei; Radu-Cristian Moldovan; Maria Ilieș; Raul Nicoară; Simona-Codruța Hegheș; Alina Uifălean; Cristina-Adela Iuga (MDPI AG, 2022)
The full understanding of the complex nature of cancer still faces many challenges, as cancers arise not as a result of a single target disruption but rather involving successive genetic and epigenetic alterations leading to multiple altered metabolic pathways. In this light, the need for a multitargeted, safe and effective therapy becomes essential. Substantial experimental evidence upholds the potential of plant-derived compounds to interfere in several important pathways, such as tumor glycolysis and the upstream regulating mechanisms of hypoxia. Herein, we present a comprehensive overview of the natural compounds which demonstrated, in vitro studies, an effective anticancer activity by affecting key regulators of the glycolytic pathway such as glucose transporters, hexokinases, phosphofructokinase, pyruvate kinase or lactate dehydrogenase. Moreover, we assessed how phytochemicals could interfere in HIF-1 synthesis, stabilization, accumulation, and transactivation, emphasizing PI3K/Akt/mTOR and MAPK/ERK pathways as important signaling cascades in HIF-1 activation. Special consideration was given to cell culture-based metabolomics as one of the most sensitive, accurate, and comprising approaches for understanding the response of cancer cell metabolome to phytochemicals.